The Relationship Between Educational Level And Community Behavior With Household Waste Management In Ihung Geulumpang Village, Kuala Batee District, Aceh Barat Regency In 2022 - Ulva Musliza; Siti Maysaroh Fitri Siregar; Maizaduana, Maizaduana; Darmawan, Darmawan (Sean Institute, 2024)
Waste management aims to reduce health and environmental impacts. Waste management consists of storage, collection and disposal. Inefficient waste management can damage the environment. In 2022, this project will examine how education influences community behavior in managing household waste in Lhung Geulumpang Village, Kuala Batee District, Southwest Aceh Regency. This research uses a descriptive quantitative cross-sectional method. This research collected data using questionnaire- based interviews from October to November 2022. The level of community education has a positive effect on waste management behavior, based on the results of bivariate analysis. The alternative hypothesis is accepted because the P value is 0.001, below 0.05.